Linking e-leadership to innovative and proactive work behaviors in tourism higher education institutions: a moderated mediation model using SEM - Heba Said; Noha Ahmed Kamel (Tourism & Management Studies)
E-leaders should encourage academics to manage their multi-dimensional work requirements and even to go beyond these requirements to innovate in their tasks and achieve sustainable development in educational institutions. This study aims to examine the relationship between e-leadership, innovative work behavior and proactive work behavior in the presence of work engagement as a mediator. Researchers implemented a quantitative methodology. This study used data from an online survey of 398 academics in Egyptian tourism higher education institutions. The results of structural equation modeling presented strong support for the proposed model. E-leadership has been proven to affect innovative and proactive work behavior among academic staff positively. Work engagement has shown an effective and significant mediating role between the examined variables. Further, the academic department was proven to moderate the relation between e-leadership and innovative work behavior, while age had no moderation effect in this relation. The study draws researchers’ attention to the role of e-leadership in helping academics to cope with the dynamic nature of research and education.